MENINGKATKAN KETERAMPILAN SOSIAL DAN KERJASAMA ANAK MELALUI ULAR NAGA DI KB AL MARDHIYYAH SAMARINDA - Arca, Yuni; Syafrina, Rizqi; reni ardiana (Teacher Training and Education Faculty, of Widya Gama Mahakam Samarinda University, 2024)
The lack of social skills and cooperation of the children contributes to internalization problems among the children. Children who tend to behave individually, have difficulties getting along with others, aggressive and difficult to control, are included in this category. According to study conducted at KB Al Mardhiyyah, social skills of the students were still problematic. It was found that students had a lack of self-awareness when it came to apologizing to and forgiving friends, and that they had no sense of responsibility or concern for their fellow friends. This observation led the researcher to develop ideas, suggestions, or plans for conducting classroom action research. The purpose of this Classroom Action Research (CAR) was to improve children's social skills and cooperation through activities such as a dragon snake game. In this study, 35 students were included as subjects of the study. Classroom Action Research was carried out in two cycles. In each cycle, there were four steps: planning, action, observation, and reflection. Based on the results of this study, we concluded that learning through dragon snake game improved social skills and cooperative of the students at KB Al Mardhiyyah Sungai Pinang Samarinda, as seen from the comparison of observations made prior to the action/pre-cycle, cycle 1 and cycle II. The results of these influences can be seen from the success indicators, which reached 77.42% from the previous success percentage of just 52.86 Keywords: social skills, cooperation, dragon snake game